The impact of drug-addicted workers on decreased job performance: A survey study of a sample of workers in selected ministries in Baghdad (Entrepreneurship Journal for Finance and Business, 2024)
The study aimed to know the role of drug-addicted workers in reducing job performance in its dimensions (non-adherence to work hours, misconduct, and low employee productivity). To achieve the study objectives, the descriptive analytical approach was adopted. A questionnaire consisting of (31) paragraphs was developed, and a random sample was drawn so that the study sample consisted of (146) workers in a selected ministry from Baghdad (Ministry of Higher Education, Ministry of Health, Ministry of Environment, Ministry of Planning). The descriptive analytical approach was relied upon, and the results were analyzed using the (SPSS) program and descriptive statistics tools. It was concluded that most of the sample members agreed that workers in the ministries surveyed have low drug use and that the job performance of workers in the ministries is good due to the low drug use by workers and that drug-addicted workers cause a decrease in job performance and that this decrease is reflected in the form of frequent absence, misconduct, and low productivity. The most prominent recommendations were the need to conduct awareness courses and implement programs to eliminate addiction in the workplace.